The Effects of Perceived Severity 0f Violation and Perceived Corporate Social Responsibility on Boycott Towards Halal Products - Muhamad Azrin Nazri; Nor Asiah Omar; Sumaiyah Abd Aziz (Universiti Sains Islam Malaysia, 2024)
e-Proceedings of The 9th Islamic Banking, Accounting and Finance International Conference 2020 (iBAF2020) “Navigating the New Normal in Islamic Finance and Wealth Management” 10th – 11th November 2020, Malaysia Organized by: Faculty of Economics and Muamalat,USIM Page: 232-233